TECHNOLOGY-DRIVEN PR MANAGEMENT OF THE INSTITUTION CONCERNING EFFICIENT INFORMATION DISSEMINATION ON THE INSTITUTIONAL LEVEL IN THE BAN-PDM EAST JAVA. - fadiyatus silmiya (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2026)
The emergence of information technology has greatly affected the practices of PR even in the public institutions like BAN-PDM East Java. This research paper will evaluate the adoption of technology based PR management and how it is effective in sharing institutional information. An in-depth interview, observation and analysis of documents were used to conduct a qualitative study in a descriptive approach. The results have shown that using the different digital platforms like SISPENA, SI-NADITA, Tata Kelola, and social media tools like Instagram and YouTube promote the speed, coverage, and precision of information that has been passed across to educational establishments and the community. Transparency is also enhanced by technology, which makes the administration of accreditation easier and helps in internal coordination using WhatsApp Groups, Telegram, and Zoom Meeting. Nevertheless, it is still ineffective due to the digital literacy differences, the lack of human resources, and the discrepancy in the management of content and the administrative publication rates. In general, this research establishes that digitalizing communication is one of the strategic measures to enhance the work of the BAN-PDM PR agency, yet organizational capacity should be enhanced to achieve the best outcome.